2016
DOI: 10.1016/j.expthermflusci.2016.03.028
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental and numerical investigation of coherent structure dynamics on mass transfer in a separated cavity flow

Abstract: This study presents the experimental and numerical investigation of coherent structure dynamics on mass transfer in a separated cavity flow. The flow field dynamics of a cavity type stagnation zone with a length to width ratio of 2 were studied. The cavity was driven by a channel flow with a Reynolds number of 1.8E5. The study utilized flow visualization, laser doppler velocimetry (LDV) and electrical conductivity probe measurements. Measurements of mean velocity and turbulence intensity profiles across the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 63 publications
0
1
0
Order By: Relevance
“…Wahba [5] reported that for Re = 35,000, a thin boundary layer along the walls of the cavity is created and a central flow which resembles a non-viscous rotating vortex with uniform vortices. Bhuiyan et al [6] shown that the coherent structures in the separated shear layer enhanced the mass transport process from the stagnation zone and the recirculation flow in the cavity affect the development of those structures. Oudina and Bessaïh [7] presented the effects of nanofluid solid volume fraction on hydrodynamic and thermal characteristics for the Rayleigh number ranges from 10 3 to 10 6 and solid volume fraction ranges from 0 to 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…Wahba [5] reported that for Re = 35,000, a thin boundary layer along the walls of the cavity is created and a central flow which resembles a non-viscous rotating vortex with uniform vortices. Bhuiyan et al [6] shown that the coherent structures in the separated shear layer enhanced the mass transport process from the stagnation zone and the recirculation flow in the cavity affect the development of those structures. Oudina and Bessaïh [7] presented the effects of nanofluid solid volume fraction on hydrodynamic and thermal characteristics for the Rayleigh number ranges from 10 3 to 10 6 and solid volume fraction ranges from 0 to 0.1.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28] Although these techniques require subjective and ultimately qualitative observations of dynamic behavior, their implementations are very simple. A virtual tuft technique has also been developed to visualize the velocity fields obtained by computational fluid dynamics (CFD) calculations because tufts are easy to understand and computationally simple.…”
Section: Introductionmentioning
confidence: 99%